An Analysis of Stated Insurance Coverage and Estimated Patient-Incurred Costs of Treatments for Lower Urinary Tract Symptoms. Issue 2 (February 2023) - Khalfay, Nuha; Lo, Eric; Grisales, Tamara; Ackerman, A. Lenore
Abstract : Importance: Lower urinary tract symptoms (LUTSs) affect more than half of all adults, yet clinical care remains poor. Anecdotally, patients and health care providers express frustration over obstacles from insurance providers to obtaining LUTS treatment; however, little information concerning actual patient-incurred costs for these medications is available. Objectives: This study aimed to analyze coverage by 5 major insurance companies and patient costs for LUTS pharmacotherapy. Study Design: For each of 5 major nationwide insurance providers (Aetna, Blue Cross/Blue Shield, Cigna, Humana, United HealthCare), formulary coverage of medications for overactive bladder, interstitial cystitis/bladder pain syndrome, and genitourinary syndrome of menopause were reviewed for low- and high-cost plans. When not covered, the best preinsurance cash price of medications was determined from GoodRx. Results: This qualitative analysis demonstrates that no guideline-directed therapy was universally covered by all insurance providers at low cost, regardless of the availability of generic alternatives. Medication prices ranged from 3 to 900 per month across plans. Inconsistencies in coverage and medication prices were common across insurance providers, between similar medications used for treatment of a given condition, and between a provider's low- and high-cost plans. Conclusions: Even medications that are U.S. Food and Drug Administration–approved and indicated by guidelines can have patient costs that are prohibitive. Because lack of care for LUTSs profoundly affects quality of life, the ability to live independently, and overall morbidity, improved price transparency is required to understand the health implications of limited coverage on LUTS care.